Derivation and characterization of porcine vocal fold extracellular matrix scaffold. (15th September 2015) - Wrona, Emily A.; Peng, Robert; Born, Hayley; Amin, Milan R.; Branski, Ryan C.; Freytes, Donald O.
Abstract : Objectives/Hypothesis: To optimize decellularization of porcine vocal folds (VF) and quantify human bone marrow‐derived mesenchymal stem cell (BM‐MSC) interactions with this matrix to provide a foundation for regenerative approaches to VF repair. Study Design and Methods: Vocal folds were dissected from porcine larynges and three decellularization protocols were compared, each consisting of washes and mechanical agitations with different combinations of reagents. DNA content was analyzed via Quant‐iT Picogreen assay and hematoxylin and eosin staining. Bone marrow‐derived MSCs were then seeded onto the decellularized VF matrices. Morphology, metabolic activity, DNA content, and gene expression were assessed using LIVE/DEAD Cell Viability, alamarBlue Cell Viability Assay, Quant‐iT Picogreen assay, and quantitative polymerase chain reaction, respectively. Results: The most successful decellularization protocol removed 95% DNA content within 1 day, compared to several days required for previously described protocols. Histology confirmed the retention of extracellular matrix (ECM) and its components, including glycosaminoglycans, collagen, and fibrin, while void of nuclear/cellular content. Decellularized scaffolds were then seeded with BM‐MSCs. Similar DNA quantities were observed after 24 hours of seeding within the VF‐ECM scaffold when compared to cells on tissue culture plastic (TCP). LIVE/DEAD staining of the seeded VF‐ECM confirmed excellent cell viability, and the metabolic activity of BM‐MSCs increased significantly on VF‐ECM compared to TCP. Endoglin gene expression decreased, suggestive of differentiation. Conclusion: Porcine VFs can be efficiently decellularized within 5 hours using a combination of sodium deoxycholate and peracetic acid. Decellularized VF‐ECM supported attachment and growth of human BM‐MSCs, with evidence of differentiation. Level of Evidence: N/A Laryngoscope, 126:928–935, 2016